Jan ze Stobnicy (ok. 1470–1518), Arystoteles i Biblia. O duszy, Bogu i Aniołach - Zawadzki, Robert K. (Collectanea Philologica, 2023)
In the article the author explores the reﬂections of Jan of Stobnicy on the soul. A group of Aristotelian notions became important categories in the Polish writer`s lectures, and the terms such as substance, essence, matter and form grew into fundamental conceptions used by Jan of Stobnica to describe the soul. The soul is the form of a living being – the spiritual part of plants, beasts and humans. That is the reason why the Polish writer, like Aristotle, posited three kinds of soul: the vegetative soul, the sensitive soul and the rational soul. Humans have a rational soul. The article presents a consideration that interrogates the ancient lore to uncover the ways in which the Bible and the Greek philosophers created images of God and angels as spiritual beings. Via a survey of Aristotelian sources about the Jan’s of Stobnica reﬂections on the soul and a study of his views of God and angels, the article reveals how this author was innovatory for the Polish philosophy.